Formulation of Inoculum a white oyster Mushroom (Pleurotus ostreatus) on powder - Khadijah; Umrah; Orryani Lambui (Biocelebes, 2019)
The study about the formulation of inoculum a white oyster mushroom (Pleurotus ostreatus) on flour. was conducted at Biotechnology laboratory of Departement , Faculty of Mathematic and Natural Science, Tadulako University. This study were aimed to oyster mushroom on production. on and to abridge the cycle of oyster mushroom production process of white.peplication used Compeletely Randomized Design (CRD) consist of six treatments and tree by comparing between (sawduts,rice,bran, and comflour) P1(50% : 27% : 23% , P2 (50% : 30% : 20%), P3 (50% : 33% : 17%), P4 (50% : 36% : 14% ), P5 (50% : 39% : 11%), P6 (50% : 42% : 8%). There are four parameters used in this study (1) .The growth of white oyster mushroom inoculum (2) the incubation time. and, (3) coloni forming unit (CFU), (4) Viability test .The resulth showed that the best growth mycelium was 1,3cm/days with incubation period was 26 days, the highest total of CFU in P5 was 12,7x 108 CFU/ml and was in P3 was 3,3 x 108 CFU/ml .The inoculum viability test of production media in P5, was faster in incubation period is 18 days.